Biventricular Endomyocardial Fibrosis associated with Ulcerative Colitis: a case report - Borges, José Victor da Nóbrega; Leila, Samira Abdel Correia; Machado, Manuella Guedes da Nóbrega (Brazilian Journal of Case Reports, 2024)
Endomyocardial Fibrosis (EMF) is a restrictive cardiomyopathy characterized by the fibrotic involvement of the endomyocardium. Describe an uncommon case and the general aspects of this entity. A 13-year-old female patient was admitted with a suspect of acute gastroenteritis. Cursed with intense protein depletion and deteriorating health conditions. During the investigation was diagnosed with Ulcerative Colitis. The Doppler echocardiogram showed hyperrefingent images and a tumoration-sugestive lesion in both ventricles. The cardiac magnetic resonance confirmed the presence of tumorations in the apical portion of right and left ventricles. The patient was submitted to a biventricular resection of the masses. After the intervention, clinical therapy was started. The diagnosis of EMF was later confirmed on the histopathologic examination. The clinical presentation of EMF is unspecific and difficult to recognize, demanding deep investigation skills. The correlation with imaging exams for diagnosis is essential, especially the echocardiogram and the magnetic resonance. In this case, it is observed the association between Ulcerative Colitis and EMF, as well as the potential of the imaging modalities in the confirmation and therapeutic guidance of this pathology.